A plasma microRNA signature of acute lentiviral infection: biomarkers of CNS disease - WITWER, Kenneth W (2011)
OBJECTIVE: Plasma microRNAs are modulated during disease and are emerging biomarkers; they have not been characterized in HIV infection. Using our macaque/simian immunodeficiency virus (SIV) model of HIV, we sought to identify a plasma miRNA profile of acute lentiviral infection, evaluate its relationship with known cellular and viral determinants of lentivirus-associated CNS disease, and explore the potential of miRNAs to predict CNS disease. DESIGN: Plasma samples were obtained pre-inoculation and ten days post-inoculation from SIV-infected macaques. METHODS: Plasma miRNA expression profiles were determined by TaqMan low density array for six individuals. miRNA expression was compared with levels of cytokines, virus, and plasma platelet count. miRNA results were confirmed by single miRNA-specific assays for ten macaques. Nineteen individuals were used to validate a disease prediction test. RESULTS: A 45-miRNA signature of acute infection (differential expression with p<0.05 after multiple comparison correction) classified plasma as infected or not. Several differentially expressed miRNAs correlated with CNS disease-associated cytokines IL-6 and CCL2 and included predicted and/or validated regulators of the corresponding mRNAs. miRNAs tracked with viral load and platelet count, also predictors of CNS disease. At least six miRNAs were significantly differentially expressed in individuals with severe versus no CNS disease; in an unweighted expression test, they predicted CNS disease. CONCLUSIONS: Acute-phase differential expression of plasma miRNAs predicts CNS disease and suggests that CNS damage or predisposition to disease progression begins in the earliest phase of infection. Plasma miRNAs should be investigated further as leading indicators of HIV diseases as early as acute infection.